Zero Waste to Landfill: Pendampingan Inisiasi Konversi Sampah Dapur Menjadi Pakan Ikan Pelet di TPST Al-Huda Curah Grinting Kecamatan Kanigaran Kota Probolinggo - Arbie Suwandana Putra; Ifani Mulya Agustianingsih; Agus Setiawan (LPPM Universitas Yudharta Pasuruan, 2019)
Garbage is still a serious problem in every region, including in the City of Probolingggo, East Java, Indonesia. Waste generation in Probolinggo City that enters the Landfill (TPA) is recorded at 65 tons/day with an increase of 10 - 11 percent per day. The synergy between TPST, Garbage Bank, and community behavior patterns in disposing of waste has not been able to reduce the volume of waste generation to the TPA significantly. Through community development, PT. Kutai Timber Indonesia synergizes with TPST Al-Huda to initiate the conversion of kitchen waste into pellet fish feed at TPST Al-Huda Curah Grinting Kecamatan Kanigaran Probolinggo City. This initiative is one of the environmental management movements that have added value for improving the community's economy. This program is the result of a strategic partnership between PT. KTI Probolinggo with TPST Al-Huda which is based on the principle of achieving environmental excellence which is carried out by creating shared values ​​based on stakeholder partnerships and adhering to the triple bottom line principle (profit, people, planet. The results of this assistance shows that TPST has been able to manage kitchen waste of up to 11 tons/month to be converted into pellet fish feed products reaching 18 tons / month.